PENJATUHAN PUTUSAN PIDANA OLEH HAKIM TERHADAP PENYALAHGUNAAN NARKOTIKA BAGI DIRI SENDIRI - Warapsari, Nesya; Soeskandi, Hari (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The purpose of this paper is to find out and explain about the judge’s considerations in giving penalties for Class I Narcotics Addicts, that is marijuana, which is stated in the Putusan Pengadilan No. 761/Pid/Sus/2021/PN Jmr. This paper refers to several approaches, such as case, statue, and conceptual approach, with normative research. The narcotics abuse case are resolved by providing guidance and care in the form of rehabilitation, not by imprisonment. However, in some cases, the are differences in resolving the case. The example of a narcotics abuse case that was resolved by imprisonment is the case by Mohammad Rifki Ananda, which is stated in the Putusan Pengadilan No. 761/Pid/Sus/2021/PN Jmr. The judge decide to resolved the case by imprisonment for 1 year, not by a medical or social rehabilitation. about Narcotics, in Pasal 54, states that medical and social rehabilitation are solutions that must be fulfilled by narcotics addicts and victims of narcotics abuse. Then, Undang-Undang No. 35 Tahun 2009 Pasal 103 also states that Majelis Hukum should order the defendant to take the rehabilitation as the settlement. The provision of rehabilitation for addicts and narcotics abuser is also strengthened by Surat Edaran Mahkamah Agung No. 04 Tahun 2010. Thus, it can be concluded that referring to Putusan Pengadilan No. 761/Pid/Sus/2021/PN Jmr, the judge did not give consideration and attention, and did not interpret all the Ayat in Pasal 127